2021
DOI: 10.1159/000515823
|View full text |Cite
|
Sign up to set email alerts
|

Complement in Renal Disease as a Potential Contributor to Arterial Hypertension

Abstract: <b><i>Objective:</i></b> Complement deposition is prevalent in kidney biopsies of patients with arterial hypertension and hypertensive nephropathy, but an association of hypertension and complement deposition or involvement of complement in the pathogenesis of hypertensive nephropathy has not been shown to date. <b><i>Methods:</i></b> In this study, we analyzed complement C1q and C3c deposition in a rat model of overload and hypertension by subtotal nephrectomy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We have observed the deposition of complement components in renal biopsy from patients and animals with hypertensive kidney disease in both previous clinical practice and literature reports (67,68). And clinical trials have shown that serum C3 are paralleled with systolic blood pressure (69,70).…”
Section: Hypertensive Kidney Diseasementioning
confidence: 81%
“…We have observed the deposition of complement components in renal biopsy from patients and animals with hypertensive kidney disease in both previous clinical practice and literature reports (67,68). And clinical trials have shown that serum C3 are paralleled with systolic blood pressure (69,70).…”
Section: Hypertensive Kidney Diseasementioning
confidence: 81%
“…In regard to the clinical utility of this biomarker, CD26 has been investigated towards ischemia-reperfusion injury in the kidneys and its potential role in suppression of apoptosis and inflammation. Moreover, CD26/DPP-4 inhibitors have been assessed and investigated for their nephroprotective role in glycemic management to reduce the incidence of micro- or macroalbuminuria in type 2 diabetes patients [ 115 , 116 , 117 ]. Lately, urinary exosomal CD26 has been investigated to see whether it can predict renal reversal and recovery from AKI.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the origin of tubular casts, formalin-fixed paraffin-embedded sections were stained for uromodulin using a mouse antihuman uromodulin (a gift from Professor J. Scherberich, LMU München, Germany) and a standard protocol for immunohistochemistry as described previously. 19 Histologic changes assessed explicitly for the quantification were glomerulosclerosis (GS), TA, IF, tubulitis, and interstitial mononuclear inflammation. Quantification of histologic changes was performed based on the percentage of total area affected by tubulointerstitial lesions and the percentage of sclerosed glomeruli.…”
Section: Biopsy Reviewmentioning
confidence: 99%